1999
DOI: 10.1111/j.1778-428x.1999.tb00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Perisurgical Intravenous Iron Therapy

Abstract: SUMMARY There is no doubt that the developments in detecting viral antigens and antibodies, and very recently viral RNA or DNA, in donor blood, have greatly increased the safety of blood transfusion1. However, while it is generally agreed that a residual risk of transmitting viral infections by blood still exists 2, we do not know if Creutzfeld‐Jakob disease or its new form – undetectable with current screening methods – are transmitted by transfusion or not 3. Furthermore, the long‐term immunomodulatory effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Recently, some authors have suggested a role for intravenous iron in correcting anaemia after orthopaedic and oncological surgery, and in renal and obstetrics patients [10][11][12], but this remains controversial in cardiac surgery [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some authors have suggested a role for intravenous iron in correcting anaemia after orthopaedic and oncological surgery, and in renal and obstetrics patients [10][11][12], but this remains controversial in cardiac surgery [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Anaphylactic reactions have been reported after the administration of intravenous iron dextrane [15]. Venofer ® (iron(III)-hydroxide sucrose) is a new intravenous preparation with very few reported side effects [10,11,16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, guidelines recommend that physicians consider intravenous (iv) iron administration in pregnant women in case of severe iron deficiency anemia (Hb -9.0 g/ dL), intolerability to oral iron, insufficient Hb increase after oral iron treatment or if there is a need for rapid Hb reconstitution. 9,10 Parenteral therapy promises a better response in anemic patients and can obviate the need for blood transfusions in the antenatal and postpartum period. 11 The most commonly used intravenous (iv) iron preparation is iron sucrose.…”
Section: Introductionmentioning
confidence: 99%